The independence of expression and identity in face-processing: evidence from neuropsychological case studies - Bate, Sarah; Bennetts, Rachel (Frontiers in Psychology, 2015)
The processing of facial identity and facial expression have traditionally been seen as independent – a hypothesis that has largely been informed by a key double dissociation between neurological patients with a deficit in facial identity recognition but not facial expression recognition, and those with the reverse pattern of impairment. The independence hypothesis is also reflected in more recent anatomical models of face-processing, although these theories permit some interaction between the two processes. Given that much of the traditional patient-based evidence has been criticised, a review of more recent case reports that are accompanied by neuroimaging data is timely. Further, the performance of individuals with developmental face-processing deficits has recently been considered with regard to the independence debate. This paper reviews evidence from both acquired and developmental disorders, identifying methodological and theoretical strengths and caveats in these reports, and highlighting pertinent avenues for future research.